Therapeutic alternatives in diabetic foot patients without an option for revascularization: a narrative review - Rümenapf, Gerhard; Morbach, Stephan; Sigl, Martin (Journal of Clinical Medicine, 2022)
Background: The healing of foot wounds in patients with diabetes mellitus is frequently complicated by critical limb threatening ischemia (neuro-ischemic diabetic foot syndrome, DFS). In this situation, imminent arterial revascularization is imperative in order to avoid amputation. However, in many patients this is no longer possible (“too late”, “too sick”, “no technical option”). Besides conservative treatment or major amputation, many alternative methods supposed to decrease pain, promote wound healing, and avoid amputations are employed. We performed a narrative review in order to stress their efficiency and evidence. Methods: The literature research for the 2014 revision of the German evidenced-based S3-PAD-guidelines was extended to 2020. Results: If revascularization is impossible, there is not enough evidence for gene- and stem-cell therapy, hyperbaric oxygen, sympathectomy, spinal cord stimulation, prostanoids etc. to be able to recommend them. Risk factor management is recommended for all CLTI patients. With appropriate wound care and strict offloading, conservative treatment may be an effective alternative. Timely amputation can accelerate mobilization and improve the quality of life. Conclusions: Alternative treatments said to decrease the amputation rate by improving arterial perfusion and wound healing in case revascularization is impossible and lack both efficiency and evidence. Conservative therapy can yield acceptable results, but early amputation may be a beneficial alternative. Patients unfit for revascularization or major amputation should receive palliative wound care and pain therapy. New treatment strategies for no-option CLTI are urgently needed.